2015
DOI: 10.3390/md13085276
|View full text |Cite
|
Sign up to set email alerts
|

The Mucus of Actinia equina (Anthozoa, Cnidaria): An Unexplored Resource for Potential Applicative Purposes

Abstract: The mucus produced by many marine organisms is a complex mixture of proteins and polysaccharides forming a weak watery gel. It is essential for vital processes including locomotion, navigation, structural support, heterotrophic feeding and defence against a multitude of environmental stresses, predators, parasites, and pathogens. In the present study we focused on mucus produced by a benthic cnidarian, the sea anemone Actinia equina (Linnaeus, 1758) for preventing burial by excess sedimentation and for protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 77 publications
3
55
1
Order By: Relevance
“…It was considered that this difference was related to the containing higher levels of protein and also being a complex mixture of proteins and polysaccharides of mucus produced by A. equina. Stabili et al, (2015) claimed that the lipid level of mucus produced by A. equina was 0.9 %. It was concluded that the containing low value in lipid level of A. equina like other marine invertebrates was characteristic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was considered that this difference was related to the containing higher levels of protein and also being a complex mixture of proteins and polysaccharides of mucus produced by A. equina. Stabili et al, (2015) claimed that the lipid level of mucus produced by A. equina was 0.9 %. It was concluded that the containing low value in lipid level of A. equina like other marine invertebrates was characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has not been found any research about the proximate composition and fatty acid profile of the species A. equina along the Northeastern Mediterranean Coast. Few researches about the chemical compositions of A. equina have been investigated in other different regions than Mediterranean Sea Stefanov et al, 1992;Stabili et al, 2015). The chemical composition of the tissue of marine species is defined as the determination of macro and micro level of the components.…”
Section: Introductionmentioning
confidence: 99%
“…Mucous may play a role in allorecognition by cnidarians, for example by promoting the discharge of nematocytes against other species while inhibiting the discharge when encountering the same species or other tentacles from the same organism (Ertman & Davenport, 1981;Gundlach & Watson, 2018). It may also have a direct alleloptahic role, causing damage to target organisms (Chadwick, 1988), and may contain bioactive molecules or toxins (Stabili, Schirosi, Parisi, Piraino, & Cammarata, 2015). It is noteworthy that some of the most aggressive corals, including Galaxea fascicularis, are known to produce copious amounts of mucous (Brown & Bythell, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This act causes localised necrosis on the recipient, but also has the unavoidable effect of ripping holes in the acrorhagi of the attacker, such that both individuals may be susceptible to infection. It has recently been demonstrated that the mucus produced by A. equina as a protective coating against desiccation and other environmental stressors contains antimicrobial properties (Stabili et al, 2015). One such property is a lysozyme-like enzyme that acts as an antibacterial agent, degrading the cell walls of gram-positive bacteria such as Micrococcus lysodeikticus.…”
Section: Introductionmentioning
confidence: 99%